Antecedents Analysis of Purchase Intention - Rowlan Takaya (Universitas Trisakti, 2016)
The advancement of technology has resulted in the creation of a new form of shopping transactions. This technology is used by residents to shop online. Thus, customers’ involvements in online purchasing have become an important trend. The objective of this research was to identify the determinants of customer purchases online. This study used a surveymethod using questionnaires and the target is an online customer in Central Jakarta.This research used simple regression to determine the effect of purchace intention to factors that influence it. Data questionnaire distributed directly to the respondents who never buy online shopping. Findings revealed that impulse purchase intention, quality orientation, brand orientation, online trust and prior online purchase experience were positively related to the customer online purchase intention.